SYSTEMATIC LITERATURE REVIEW: HUBUNGAN VARIABEL DIGITAL MARKETING TERHADAP KINERJA PEMASARAN - Vivi Herlina; Syahmardi Yacob (Universitas Halu Oleo, 2022)
The advancement of information technology requires a business to utilize it; one of the utilizing of information technology to maximize marketing is using digital marketing. This study aims to answer the research question; what is the role of digital marketing in affecting marketing performance. The method was Systematic Literature Review by searching papers or proceedings published between 2015-2021. The result shows that most data analyzing methods are Structural Equation Modelling and multiple regression. From the papers is known that e-marketing digital marketing capabilities variables affect marketing performance.